elk1/miR-462-731 Feedback Loop Regulates Macrophages Polarization and Phagocytosis in Grass Carp (Ctenopharyngodon idella) - He, Yan; Liu, Yuting; Yang, Yuyue; Liu, Yang; Jia, Xuewen; Shen, Yubang; Xu, Xiaoyan; Li, Jiale (Frontiers in Immunology, 2022)
MicroRNA clusters are microRNAs (miRNAs) that are distributed in close proximity on chromosomes. In this study, we report an miRNA cluster identified from grass carp (Ctenopharyngodon idella), miR-462-731, which plays a positive role in host antibacterial immunity. The expression of miR-462-731 was disrupted after infection by Aeromonas hydrophila. Transcription factor ETS transcription factor elk1 (elk1) was identified to bind to the promoter of the miR-462-731 cluster and suppress its expression. In addition, miR-731 negatively regulates the expression of elk1, forms a elk1/miR-462-731 double negative feedback loop. In addition, we found that miR-731 directly targets ezra to induce macrophage polarization to the M1 phenotype with stronger phagocytosis. Our results demonstrate a novel elk1/miR-462-731 feedback loop. The data deepen our understanding of the relationship between macrophage polarization and phagocytosis in teleost fish.